Deserving to Whom? Investigating Heterogeneity in the Impact of Social Constructions of Target Populations on Support for Affirmative Action. Issue 1 (15th May 2019) - Bell, Elizabeth
Abstract : The social construction of target populations has emerged as an influential framework for understanding the public policy process. In particular, target populations have been shown to shape the allocation of benefits and burdens by political elites. However, existing studies focus on the elite level, which overlooks whether public preferences are aligned with the allocation of policy benefits and burdens by political elites. Moreover, many studies treat social constructions as homogenous, which this paper calls into question. Using a nation‐wide survey experiment, I investigate variation in public support for affirmative action policies with randomly assigned target populations. The findings indicate that the public formulates policy preferences on the basis of perceived deservingness of target groups similar to political elites. In addition, the findings uncover heterogeneity in the effect of targeting on public opinion based on ideology and racial/ethnic group identity. Abstract : 对目标人群的社会建构已成为理解公共政策过程的重要框架。具体来说，现有研究已证明目标人群可以影响政治精英对利益和负担的分配。然而，现有研究将重点放在了精英层面，而忽视了公众偏好是否与政治精英对政策利益和负担的分配相一致。此外，许多研究认为社会建构是同质的，本文对此提出了质疑。本研究进行了一项全国范围的调查实验，根据随机分配的目标人群，我们对平权法案政策的公众支持差异进行了研究。研究结果表明，与政治精英类似，公众会依据他们对目标群体的感知价值来形成他们的政策偏好。此外，我们的研究结果发现，这种作用于公众意见的影响会因意识形态和种族或族群身份而产生差异。